2021
DOI: 10.3390/children8020150
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Mental Health as a Factor Associated with Exclusive Breastfeeding and Breastfeeding Duration: Data from a Longitudinal Study in Greece

Abstract: This study investigated the relationship between exclusive breastfeeding and breastfeeding duration, and maternal psychological well-being in the perinatal period. Methods: A longitudinal study involving a retrospective follow-up of a group of 1080 women from pregnancy to the 1st year postpartum, who gave birth during the 5-year period between January 2014 and January 2019 in Athens, Greece, was designed. Women’s history and two psychometric tools—the Edinburg Postpartum Depression Scale (EPDS) and the Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 75 publications
0
10
0
1
Order By: Relevance
“…It is known that breastfeeding is a protective factor for the mother against postpartum stress and depression development. A recent study by Dagla et al [13] confirmed that breastfeeding and its duration could positively influence maternal mental health, demonstrating how a shorter duration of breastfeeding is related to symptoms of psychological distress, initiation of psychological therapy, and higher scores on the Edinburgh Postpartum Depression Scale. Previous studies have obtained similar results, confirming the association between breastfeeding and maternal mental health [14].…”
Section: Support Of Breastfeeding During the Covid-19 Pandemicmentioning
confidence: 99%
“…It is known that breastfeeding is a protective factor for the mother against postpartum stress and depression development. A recent study by Dagla et al [13] confirmed that breastfeeding and its duration could positively influence maternal mental health, demonstrating how a shorter duration of breastfeeding is related to symptoms of psychological distress, initiation of psychological therapy, and higher scores on the Edinburgh Postpartum Depression Scale. Previous studies have obtained similar results, confirming the association between breastfeeding and maternal mental health [14].…”
Section: Support Of Breastfeeding During the Covid-19 Pandemicmentioning
confidence: 99%
“…Perinatal mental health indicators encompass the spectrum of mental health indicators (including and not limited to adjustment disorders and distress, PTSD, mild to moderate depressive illness, severe depressive illness, chronic severe mental illness and postpartum psychosis). Such conditions are associated with adverse breastfeeding outcomes and women could benefit from targeted anticipatory guidance and additional support (Dagla et al, 2021). In addition as evidence demonstrates the benefits of breastfeeding with reduction in hospitalisations and mortality both in the UK and worldwide, it is important to understand if remote support has any impact on these (Payne & Quigley, 2017; Sankar et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the diverse evidence indicating that high self-efficacy levels have the power to positively influence the maintenance of breastfeeding ( 14 ) , and that the presence of anxiety can negatively influence this practice ( 15 ) , studies that evaluate the relationship of those variables were not found in the scientific literature. That fact shows that important failures persist, which justifies the conduction of this study.…”
Section: Introductionmentioning
confidence: 99%